2016
DOI: 10.1111/ics.12372
|View full text |Cite
|
Sign up to set email alerts
|

Elastin structure and its involvement in skin photoageing

Abstract: Skin aging is a complex process that may be caused by factors that are intrinsic and extrinsic to the body. Ultraviolet (UV) radiation represents one of the main sources of skin damage over the years and characterizes a process known as photoaging. Among the changes that affect cutaneous tissue with age, the loss of elastic properties caused by changes in elastin production, increased degradation and/or processing produces a substantial impact on tissue esthetics and health. The occurrence of solar elastosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(111 citation statements)
references
References 66 publications
(122 reference statements)
5
102
0
1
Order By: Relevance
“…Among the changes that affect cutaneous tissue with age, the loss of elastic properties caused by increased elastin degradation and/or processing and changes in elastin production cause a substantial impact on tissue esthetics and health. The occurrence of solar elastosis is one of the main markers of cutaneous photoaging and is characterized by disorganized and non-functional deposition of elastic fibers [33]. In summary, as with fibrillins, our results indicate that FB per se promoted the expression of ELN in fibroblasts.…”
Section: Discussionsupporting
confidence: 58%
“…Among the changes that affect cutaneous tissue with age, the loss of elastic properties caused by increased elastin degradation and/or processing and changes in elastin production cause a substantial impact on tissue esthetics and health. The occurrence of solar elastosis is one of the main markers of cutaneous photoaging and is characterized by disorganized and non-functional deposition of elastic fibers [33]. In summary, as with fibrillins, our results indicate that FB per se promoted the expression of ELN in fibroblasts.…”
Section: Discussionsupporting
confidence: 58%
“…Elastosis, denaturation of elastin fibers, occurs with the exposure of skin to UV radiation . Previous studies have found that the occurrence of UV radiation‐induced alternative splicing of the elastin gene is a potential explanation for this phenomenon . The results of our study about elastin gene expression also provided the detail information for elastin reducing in the photoaged skin.…”
Section: Discussionsupporting
confidence: 60%
“…24 Previous studies have found that the occurrence of UV radiationinduced alternative splicing of the elastin gene is a potential explanation for this phenomenon. 25 The results of our study about elastin gene expression also provided the detail information for elastin reducing in the photoaged skin. We presume that the decrease of elastin in photoaged skin is the result of a combination of downregulation of elastin gene expression and denaturation of proper elastin fibers.…”
Section: Discussionmentioning
confidence: 61%
“…When the mechanical force is removed, elastin folds back on itself and its fibers become shortened. It goes without saying that the optimal functionality of elastin would also be dependent on adequate tissue hydration [19] .…”
Section: The Matrisome: Significance and Functionmentioning
confidence: 99%